Bifurcation Lesion - Stumpf, Christian; Chen, Shao Liang; Sheiban, Imad; Vassilev, Dobrin (wiley, 2021)
At the present time, when performing percutaneous coronary intervention (PCI) for bifurcation lesions, the main challenges are the highly variable bifurcated anatomy and the extent of myocardium in jeopardy. The provisional T-stenting strategy is currently the preferred approach in treating bifurcation lesions. The bifurcation angle is a very important factor during PCI of bifurcation lesions. Balloon angioplasty is utilized for lesion preparation of the main vessel (MV) or side branch (SB) in order to facilitate the stenting process. Provisional SB stenting is characterized by stent implantation in the MV and, when necessary, in the SB. The simultaneous kissing stents technique is the simplest and most immediate approach to treat bifurcations when two stents are needed. After deploying the stent in the MV and SB, to achieve optimal results in both vessels, kissing balloon inflation can be done with simultaneous dilatation in both branches.
CRIS-Team Scopus Importer:2024-12-04